Synergistic effect of technology and customer relationship orientations: consequences for market performance. Issue 5 (1st June 2015) - Salojärvi, Hanna; Ritala, Paavo; Sainio, Liisa-Maija; Saarenketo, Sami
Abstract : Purpose: – This study aims to examine the effect of firm-specific customer relationship orientation, technology orientation and the marketing–R & D cooperation on market performance. Although the importance of customer focus in R & D has been widely recognized in the literature, less attention has been paid to customer relationship orientation and the simultaneous effect of the three constructs on market performance. Design/methodology/approach: – The hypotheses are tested on a multi-industry survey study of 209 R & D-intensive firms in Finland using hierarchical regression analyses, including both direct and interactional effects. Findings: – The findings show that customer relationship orientation has a direct positive effect on market performance and that technology orientation also has a positive, yet non-significant effect. In addition, the effect of both of these strategic orientations is accentuated when collaboration between marketing and R & D departments is high, providing evidence on the significant moderating effects of these types of processes. Research limitations/implications: – The implications of the research can be interpreted as being generalizable at least to some extent due to the multi-industry nature of the sample. However, the research is bound to a certain type of firm (R & D-intensive) and to a certain national context (Finland), which poses limitations to the study. Practical implications: – The results suggest specific benefits for integrating specialist, complementary knowledge into a firm in terms of R & D and marketing knowledge. Practicing managers across departments should thus consider not only focusing on their specialist areas in markets (e.g. customers or technology) but also utilizing complementary insights within the firm to reap benefits in their fields. Originality/value: – The study focuses on the less-researched concept of customer relationship orientation in parallel with the more established technology orientation. It also provides novel evidence on how the effectiveness of these orientations benefits from firm-internal knowledge transfer between the marketing and R & D departments.